SEJARAH HUKUM PERADILAN DI INDONESIA - Imam Fawaid; Abd. Rahman (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2022)
Abstract Judicial power in Indonesia is a power which regulates the governance of the judicial system. The judiciary is included in the category of judicial power as a separate judicial system from other powers, namely the executive and legislative branches. The dynamics of the journey of judicial power continues to move, following the perfection of independent and perfect judicial power. From the Dutch colonial era to the independence era. The challenges are various and to organize so that the concept of judicial power is truly independent and dignified. Regulations continue to be carried out towards the perfection of independent judicial power. With the enactment of Law Number 35 of 1999, judicial institutions (except the Religious Courts which at that time were still in the Ministry of Religion) were under the Supreme Court both institutionally and administratively. This change is indicated by the spirit of realizing an independent judicial power, free from interference from other powers. since 2004 all judicial bodies have been under one roof under the authority of the Supreme Court.